ANALISIS PERBANDINGAN PERFORMANSI TRANSMISI VIDEO DENGAN UNICAST PADA WLAN IEEE 802.11ac - Faisal Faisal; Rizal Munadi; Syahrial Syahrial (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2018)
Network technology is now advancing with increasing speed of data provided. This is spurred by the rapid increase in real time data needs in various fields such as education, entertainment, sports and for business purposes. With the IEEE 802.11ac Wireless LAN technology, users will be easier to access information such as streaming video. But this is very dependent on the area of the wireless LAN network coverage available in a building or campus environment. The capture power of Access Point signals in one location will be different from other locations, so the quality of the resulting video streaming is different for each location. This study aims to analyze the performance of two different video formats, namely MPEG-4 and H.264. The research method of MPEG-4 and H.264 streaming video transmission through IEEE 802.11ac WLAN uses experimental methods for performance evaluation of two different protocols HTTP and UDP based on parameters of delay, packet loss and throughput. After doing the research, then getting the results using the HTTP protocol all the parameters are better for the H.264 format video, whereas for the UDP protocol all the parameters are better used for the type of video format MPEG 4.